Synthesis and Characterization of Vanadium Doped Zinc Oxide Thick Film for Chemical Sensor Application. (26th October 2015) - Zargar, Rayees Ahmad; Arora, Manju; Ahmad, Masroor; Hafiz, Aurangzeb Khurram
Abstract : Zinc oxide and vanadium pentoxide nanoparticles derived by chemical coprecipitation route were used to cast Zn0.96 V0.04 O thick film by screen printing method. The structural, morphological, optical, and electrical properties of the film were characterized by powder XRD, SEM, Raman, UV-VIS, and DC conductivity techniques. XRD pattern, SEM image, and Raman spectrum of the film confirm the single phase formation of Wurtzite structure with preferential orientation along [101 ] plane, minor variation in lattice parameters, and vanadium ions substitution at zinc sites. Zn0.96 V0.04 O pellet has been used for sensing ammonia vapor concentrations in 20–50°C temperature range which exhibits maximum responsiveness and sensitivity at 30°C. The minor variations in resistance are observed with ammonia vapor concentration. The adsorption of ammonia vapors through weak hydrogen bonding and its insertion into lattice by nitrogen lone pairs donation at vacant/defect sites in lattice caused by vanadium doping are considered to explain gas sensing mechanism.